Sustainability in Maritime Transport: Advances, Solutions and Pending Tasks - Orosa, José A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, "Sustainability in Maritime Transport: Advances, Solutions and Pending Tasks", provides an up-to-date overview of the use of new technologies to develop more sustainable maritime transport based on new combustibles, working procedures and related industries, all of which are in agreement with the technical limitations indicated by safety on board.